Identity Negotiation in Mixed Marriage Couples Between the Batak and Other Ethnic Without Having to Adopt a Batak’s ‘Marga’ (Clan) - Olina Hartani Muliani Gultom; Turnomo Rahardjo; Triyono Lukmantoro (Interaksi Online, 2022)
In Indonesia, there are a variety of ethnic groups, and each one has their own traditions and cultures that they uphold. But in a rapidly increasing rate of globalization and in a densely populated country, cross-cultural marriages are bound to happen and the clash between the two cultural identities are inevitable such as the clash between the Batak tribe’s ethnic’s customs and other traditions in marriage. This is the reason why identity negotiations are crucial for managing the difference in traditions when a Batak person marries outside of their ethnicity to avoid conflict. This paper investigates how Batak people and other ethnicities view their ‘Marga’ (clan) in marriage and how negotiations are conducted for those who opt to not use a ‘Marga’ (clan). The research for this paper is conducted via the phenomenological approach that is conducted on mixed marriage couples where one is of Batak descent and another is of a different ethnicity living outside North Sumatra, the data collected are qualitative through in- depth interviews. The key findings and conclusion of this paper were that the Batak identity within individuals had decreased and began to fade, especially for those that lives outside of North Sumatera and hence do not uphold their traditions anymore. Because of this, an identity negotiation has to be conducted to try and find a compromise that is fair for both parties in a mixed marriage and this process will proceed smoothly if good communication and a supporting relationship pattern are present. The findings within this paper can be used a guide for those who wish to conduct a cross-cultural marriage without giving a ‘Marga’ (clan).